2014
DOI: 10.1113/jphysiol.2014.272435
|View full text |Cite
|
Sign up to set email alerts
|

Novel roles of gastrin

Abstract: The existence of the hormone gastrin in the distal stomach (antrum) has been known for almost 110 years, and the physiological function of this amidated peptide in regulating gastric acid secretion via the CCK2 receptor is now well established. In this brief review we consider important additional roles of gastrin, including regulation of genes encoding proteins such as plasminogen activator inhibitors and matrix metalloproteinases that have important actions on extracellular matrix remodelling. These actions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 72 publications
(79 reference statements)
0
41
0
Order By: Relevance
“…That the physiological function of gastrin in regulating gastric acid secretion occurs via the CCK2R is now well established 25, 34. In recent years, however, several lines of evidence have emerged to suggest that there is much more to the biology of gastrin than is indicated by earlier work 25, 35. Gastrin has been shown to display proliferative,36, 37 antiapoptotic,38 and cell migration39 properties.…”
Section: Discussionmentioning
confidence: 99%
“…That the physiological function of gastrin in regulating gastric acid secretion occurs via the CCK2R is now well established 25, 34. In recent years, however, several lines of evidence have emerged to suggest that there is much more to the biology of gastrin than is indicated by earlier work 25, 35. Gastrin has been shown to display proliferative,36, 37 antiapoptotic,38 and cell migration39 properties.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that gastrin also regulates other important cellular pathways in the stomach including cell proliferation, migration, invasion, angiogenesis and apoptosis (recently reviewed in ref. 21) and a recent in vitro study showed that gastrin plays a key role in maintaining gastric stem cells. 22 Some of these effects arise as a result of the altered expression of proteins that regulate tissue remodelling including members of the matrix metalloproteinase, 23 tissue inhibitor of metalloproteinase 24 and urokinase plasminogen activator 25 families.…”
Section: Gastric Hormonesmentioning
confidence: 99%
“…Nevertheless, the results are provocative and consistent with another study [38] showing a weak association between acid-suppressing medication use and total number of gastric cancer cases, not broken down by anatomical subsite. A mechanistic link between the use of these medications and gastric carcinogenesis is conceivable, on the basis of the moderately elevated gastrin levels frequently found in users of these drugs and the trophic (proproliferative) effects of gastrin on the gastrointestinal mucosa [39].…”
Section: Acid-suppressing Medication Usementioning
confidence: 99%